Cloning and Sequence Analysis of Recombinant Plasmodium vivax Merozoite Surface Protein 1 (PvMSP-1(42) kDa) In pTZ(57)R/T Vector - MIRAHMADI, Hadi (Iran J Parasitol, 2015)
BACKGROUND: Carboxy-terminal 42 kDa region of Plasmodium vivax merozoite surface protein-1 is considered as an important antigen in blood stage. Since, this region has been observed to be polymorphic among isolates of P. vivax, it is significant to survey on different regions of this antigen in various areas of the world. METHODS: In the present study, the genetic diversity of cloned PvMSP-1(42) kDa gene from an Iranian patient is analyzed. Parasite DNA was extracted from a P. vivax - infected patient in Iran. The region of PvMSP-1(42) kDa was amplified by PCR, cloned into pTZ(57)R/T vector and then sequenced. RESULTS: Sequencing of cloned PvMSP-1(42) kDa gene clearly has a high degree of homology (95%) with reference Sal-I sequence and also with the homogeneous sequences from some studied countries (97%). Thirty eight SNPs (single nucleotide polymorphism) were identified in cloned PvMSP-1(42) kDa gene which the mutations had localized in the 33 kDa fragment (PvMSP-1(33) kDa), while there was nearly no variation in the 19 kDa fragment (PvMSP-1(19) kDa). 2 out of 38 mutations were found as to be novel haplotypes. CONCLUSION: High similarity of cloned PvMSP-1(42) kDa gene in comparison to reference sequence and other sequences could be beneficial as a remarkable molecular marker for serological diagnostic kits of P. vivax in malarious neighboring countries of Iran and around the world.